EPA‐Registered Repellents for Mosquitoes Transmitting Emerging Viral Disease. Issue 12 (9th December 2016) - Patel, Radha V.; Shaeer, Kristy M.; Patel, Pooja; Garmaza, Aleksey; Wiangkham, Kornwalee; Franks, Rachel B.; Pane, Olivia; Carris, Nicholas W.
Abstract : In many parts of the United States, mosquitoes were previously nuisance pests. However, they now represent a potential threat in the spread of viral diseases. The Aedes aegypti, Aedes albopictus, and Culex species mosquitoes are endemic to the United States and together may transmit a variety of viral diseases of growing concern, including West Nile virus, chikungunya, dengue fever, and Zika virus. The Centers for Disease Control and Prevention and the Environmental Protection Agency (EPA) recommend N, N ‐diethyl‐meta‐toluamide (DEET) as a first‐line mosquito repellent, but for patients refusing to use DEET or other conventional repellents, guidance is limited to any EPA‐registered product. Therefore, we conducted a systematic review of the literature to identify which EPA‐registered personal mosquito repellent provides the best protection from A. aegypti, A. albopictus, and Culex spp. mosquitoes. We abstracted data from 62 published reports of EPA‐registered mosquito repellents. The conventional repellent picaridin has the strongest data to support its use as a second‐line agent, while IR3535 and oil of lemon eucalyptus are reasonably effective natural products. Citronella, catnip, and 2‐undecanone offer limited protection or have limited data. These results can be used by pharmacists and other health care professionals to advise patients on the selection of an EPA‐registered mosquito repellent. Regardless of the repellent chosen, it is vital for patients to follow all instructions/precautions in the product labeling to ensure safe and effective use.